Therapeutic Potentials of Ketamine and Esketamine in Obsessive–Compulsive Disorder (OCD), Substance Use Disorders (SUD) and Eating Disorders (ED): A Review of the Current Literature - Giovanni Martinotti; Stefania Chiappini; Mauro Pettorruso; Alessio Mosca; Andrea Miuli; Francesco Di Carlo; Giacomo D’Andrea; Roberta Collevecchio; Ilenia Di Muzio; Stefano L. Sensi; Massimo Di Giannantonio (Brain Sciences, 2021)
The obsessive–compulsive spectrum refers to disorders drawn from several diagnostic categories that share core features related to obsessive–compulsive disorder (OCD), such as obsessive thoughts, compulsive behaviors and anxiety. Disorders that include these features can be grouped according to the focus of the symptoms, e.g., bodily preoccupation (i.e., eating disorders, ED) or impulse control (i.e., substance use disorders, SUD), and they exhibit intriguing similarities in phenomenology, etiology, pathophysiology, patient characteristics and clinical outcomes. The non-competitive N-methyl-D-aspartate receptor (NMDAr) antagonist ketamine has been indicated to produce remarkable results in patients with treatment-resistant depression, post-traumatic stress disorder and OCD in dozens of small studies accrued over the past decade, and it appears to be promising in the treatment of SUD and ED. However, despite many small studies, solid evidence for the benefits of its use in the treatment of OCD spectrum and addiction is still lacking. Thus, the aim of this perspective article is to examine the potential for ketamine and esketamine in treating OCD, ED and SUD, which all involve recurring and intrusive thoughts and generate associated compulsive behavior. A comprehensive and updated overview of the literature regarding the pharmacological mechanisms of action of both ketamine and esketamine, as well as their therapeutic advantages over current treatments, are provided in this paper. An electronic search was performed, including all papers published up to April 2021, using the following keywords (“ketamine” or “esketamine”) AND (“obsessive” OR “compulsive” OR “OCD” OR “SUD” OR “substance use disorder” OR “addiction” OR “craving” OR “eating” OR “anorexia”) NOT review NOT animal NOT “in vitro”, on the PubMed, Cochrane Library and Web of Science online databases. The review was conducted in accordance with preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The use and efficacy of ketamine in SUD, ED and OCD is supported by glutamatergic neurotransmission dysregulation, which plays an important role in these conditions. Ketamine’s use is increasing, and preliminary data are optimistic. Further studies are needed in order to better clarify the many unknowns related to the use of both ketamine and esketamine in SUD, ED and OCD, and to understand their long-term effectiveness.